Узгодження параметрів турбовентиляторної приставки трдд із заднім розташуванням вентилятора - Терещенко, Юрий Матвеевич; Гуз, С. Ю.; Терещенко, Ю. Ю. (Eastern-European Journal of Enterprise Technologies, 2009)
The task of optimization of parameters of turboventilyatornoy prefix of TRDD is examined after the condition of receipt of minimum value of specific expense of fuel for the concrete terms of flight of aircraft